Multipoverty in Venezuela: A Libertarian Approach - Acevedo, Rafael Alexis; Cirocco, Luis H; D'Andrea, Fernando Antonio Monteiro Christoph (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2018)
Poverty has been defined by several authors and international organizations from similar perspectives. However, those definitions tend to be simplistic and not powerful enough to deal with complex situations that involve different points of view on the poverty phenomenon. The aim of this paper is to use a praxeological standpoint and introduce a new definition, multipoverty, while using it to analyze the current crisis in Venezuela. Three main conclusions are drawn: in current Venezuela, all common people are very likely to be poor, and a social explosion there is possible; the nature of the human being is too complex to be analyzed under a simplistic approach based on the rigidness of pure quantitative methods; the multipoverty approach adds a humanistic, praxeological, and individualistic edge, based upon ideas of freedom of action, to the traditional definitions of poverty and helps to better understand the phenomena.